2022
DOI: 10.1007/s12529-022-10116-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Intolerance of Uncertainty, Worry, Rumination, and Distress in College Students During the Coronavirus Pandemic: the Role of COVID-19 Threat Appraisals

Abstract: Background In two conditional process models, we examined whether intolerance of uncertainty (IU) had both direct and indirect effects on coronavirus anxiety (through worry) and depressive symptoms (through rumination) among college students; these associations were hypothesized to be more likely among students who appraised COVID-19 as highly threatening. Method Data were collected during the COVID-19 pandemic from September 2020 to November 2020 in the USA. Participants (n = 134) completed measures of IU, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…The scarcity of research on the effects of IU on PWB among students living in conflict zones is notable. This study found a significant negative association between IU and PWB, consistent with previous research outside of conflict zones (Chirumbolo et al, 2022; Korte et al, 2022; Marín-Chollom & Panjwani, 2023). This is not surprising, given the frequent experience of unpredictable and uncertain events in conflict zones, which often lead to significant disruptions in daily life and result in psychological distress (Liao & Wei, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The scarcity of research on the effects of IU on PWB among students living in conflict zones is notable. This study found a significant negative association between IU and PWB, consistent with previous research outside of conflict zones (Chirumbolo et al, 2022; Korte et al, 2022; Marín-Chollom & Panjwani, 2023). This is not surprising, given the frequent experience of unpredictable and uncertain events in conflict zones, which often lead to significant disruptions in daily life and result in psychological distress (Liao & Wei, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The cross-sectional study by Zhuo et al [ 45 ] suggested that COVID-19-related intolerance of uncertainty significantly and negatively predicted MH among returning college students in Wuhan. The results above were also supported by the study by Marín-Chollom and Panjwani [ 46 ], which indicated that IU had a detrimental effect on college students’ MH during the COVID-19 pandemic. Accordingly, hypothesis 1 is proposed: the IUC of college students significantly negatively affects their MH.…”
Section: Theory and Research Hypothesessupporting
confidence: 75%
“…In other words, negative cognitions can exacerbate individuals' sense of insecurity (30). Moreover, excessive rumination about COVID-19 may also increase people's perceptions of psychological fear, which could then in uence their sense of security by heightening judgments of environmental insecurity (31). Therefore, as a maladaptive coping strategy, intrusive rumination may be negatively related to the sense of security.…”
Section: The Mediating Role Of the Sense Of Securitymentioning
confidence: 99%